Hypomorph mutation-directed small-molecule protein-protein interaction inducers to restore mutant SMAD4-suppressed TGF-β signaling. Issue 5 (20th May 2021) - Tang, Cong; Mo, Xiulei; Niu, Qiankun; Wahafu, Alafate; Yang, Xuan; Qui, Min; Ivanov, Andrey A.; Du, Yuhong; Fu, Haian
Summary: Tumor suppressor genes represent a major class of oncogenic drivers. However, direct targeting of loss-of-function tumor suppressors remains challenging. To address this gap, we explored a variant-directed chemical biology approach to reverse the lost function of tumor suppressors using SMAD4 as an example. SMAD4, a central mediator of the TGF-β pathway, is recurrently mutated in many tumors. Here, we report the development of a TR-FRET technology that recapitulated the dynamic differential interaction of SMAD4 and SMAD4 R361H with SMAD3 and identified Ro-31-8220, a bisindolylmaleimide derivative, as a SMAD4 R361H /SMAD3 interaction inducer. Ro-31-8220 reactivated the dormant SMAD4 R361H -mediated transcriptional activity and restored TGF-β-induced tumor suppression activity in SMAD4 mutant cancer cells. Thus, demonstration of Ro-31-8220 as a SMAD4 R361H /SMAD3 interaction inducer illustrates a general strategy to reverse the lost function of tumor suppressors with hypomorph mutations and supports a systematic approach to develop small-molecule protein-protein interaction (PPI) molecular glues for biological insights and therapeutic discovery. Graphical abstract: Highlights: A TR-FRET assay recapitulates variant-directed SMAD4/SMAD3 PPI dynamics uHTS reveals small-molecule SMAD4 MUT /SMAD3 PPI inducers as targeted molecular glues Bisindolylmaleimides derivatives restore SMAD4 MUT /SMAD3 interaction SMAD4 MUT /SMAD3 PPI inducers reestablish tumor-suppressive TGF-β signaling Abstract : Tang et al. report a systematic approach for unbiased discovery of small-molecule protein-protein interaction (PPI)-inducing activators as molecular glues to enhance PPIs that are attenuated by hypomorph mutations and as chemical probes for biological insights and therapeutic discovery.